Efektifitas Pendekatan Matematika Realistik Untuk Meningkatkan Kemampuan Berpikir Kritis Siswa SD dalam Pembelajaran Matematika - Puspitawedana, Dita (Jurnal Pancar, 2017)
This study was aimed to describe the effectiveness realistic mathematics approach? to improve students critical thinking in mathematics learning . This study was experimental whose subjects are students of class V SD Negeri Menganti 1 Kesugihan ?by the number of students as many as 34. The instrument used was critical thinking test consisting of multiple choice questions and descriptions. For student learning achievement test consists of multiple choice questions. The data analysis technique used is the one sample t-test with a significance level of 5% to test the effectiveness of realistic mathematics approach ?to improve students critical thinking. The results of the research showed the realistic mathematics approach was effective for improve student critical thinking and learning achievement.